A STUDY ON TEACHING READING OF ENGLISH RECOUNT TEXT TO THE EIGHT YEAR STUDENTS OF MTs NEGERI SUKOHARJO IN 2009/2010 ACADEMIC YEAR - SETIYANINGSIH , REDI (2010)
This research describes the implementation of reading teaching-learning process, problems faced by the teacher in teaching reading, problems faced by the students in learning reading and problem solving. This research uses descriptive qualitative study that uses method of observation, interview, and document. The subject of this research are the teacher and the eight year students of MTs Negeri Sukoharjo. The results of the research show that: a) the objectives of the teaching reading is to improve the reading competence of the students, b) the material used by the teacher is recount text. The teacher teaches her students use various books such as: “English on Sky”, “Let’s Talk”, and “Solusi”, c) the methods applied by the teacher are ALM, GTM, Cooperative Language Learning and Genre based Instruction. The techniques are listening, repetition, translation, explanation, and work in group, d) the teacher uses four phases in teaching reading; Building Knowledge of Field, Model of the Text, Joint Construction of the Text, and Independent Construction of the Text, e) the problems faced by the teacher are the teacher finds difficulty in explaining the content of English text, managing the students in the class, the students have low motivation, each student has different capability, and the teacher has limited time, f) the problems faced by the students are difficult to know language features in recount text, difficult in reading and translating, difficult to memorize verb 1 and verb 2, and difficult to differentiate between generic structure and language features, and g) the problem solving done by the teacher are walked around the class, the teacher has to good relationship with the students, the teacher should explain the material clearly, gives additional time, and asks the students to bring the dictionary